Dynamic behavior of CFRP strengthen RC beams based on digital image correlation technology. (August 2022) - Lu, Juan; Zhang, Yafang; Duan, Libin; Huo, Yongjie; Liu, Hao
Highlights: The dynamic behavior of CFRC strengthen RC beam was studied by three-point bending tests with a drop-hammer impact device. CFRP can significantly improve the impact resistance of beams. The DIC method was used to capture the initiation and propagation process of impact multiple-cracks. The propagation speed of impact multiple-cracks was measured based on the strain field obtained by DIC. Abstract: In this paper, impact behaviors of reinforced concrete (RC) beam and carbon fiber reinforced plastic (CFRP) strengthen RC beam (CFRP-RC beam), including the damage process, failure pattern, impact force peak value and peak deflection were investigated by means of using three-point bending tests with a drop-hammer impact device. A high-speed camera combined with digital image correlation (DIC) method was used to capture the initiation and propagation process of impact multiple-cracks and to record the cracking strain. The results showed that the changes of hammer impact height and bonded CFRP on beams had different effects on dynamic response of beams, and they also caused change of failure pattern of beams. Introduce of CFRP can significantly reduce the crack widths and mid-span deflections of beams and improve the impact resistance of beams. In addition, the crack velocity in RC beam was inhibited effectively by CFRP, however, the inhibitory effect declined as impact velocity increased.